Work-Related Deaths in Canada - Bittle, Steven; Chen, Ashley; Hébert, Jasmine (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2018)
This paper critically examines official statistics on workplace fatalities in Canada. Each year the Association of Workers’ Compensation Boards of Canada reports on the number of workers who die from a work-related injury or illness/disease. The problem, however, is that these data report the number of deaths that were accepted for compensation; it is not a system for tracking all work-related deaths. Drawing from a range of data sources and employing a broad definition of what constitutes death at work we attempt to generate a more accurate estimate of the number of work-related fatalities in Canada. In so doing our goal is not to produce a definitive number of annual deaths at work – an impossibility given the paucity of data sources – but instead to challenge dominant ways of conceptualizing what constitutes a work-related fatality and thus contribute to ongoing efforts to raise academic, political, and public awareness about this important issue. In this sense our goal is to question whether official statistics regarding workplace fatalities are complete when set against a broader understanding of what constitutes death at work.